2022
DOI: 10.1038/s41598-022-19247-9
|View full text |Cite
|
Sign up to set email alerts
|

LINC00511/hsa-miR-573 axis-mediated high expression of Gasdermin C associates with dismal prognosis and tumor immune infiltration of breast cancer

Abstract: Breast cancer (BC) is considered the second commonest human carcinoma and the most incident and mortal in the female population. Despite promising treatments for breast cancer, mortality rates of metastatic disease remain high. Gasdermin C (GSDMC) is an affiliate of the gasdermin (GSDM) family, which is involved in the process of pyroptosis. Pyroptosis is implicated in tumorigenesis, but the role of GSDMC in cancer cells is yet to be fully elucidated. In this study, we investigated the role and mechanism of GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 69 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…However, pyroptosis does not exert an absolutely positive therapeutic anticancer effect. A study revealed that elevated expression of GSDMC is also strongly associated with a worse prognosis for invasive breast carcinoma patients and exhibits a correlation with immune cell infiltration in the tumor [122]. Jianwei Gao and colleagues also found that increased GSDMD expression levels may increase the tumor size, promote more advanced tumornode-metastasis stages, and affect survival rates.…”
Section: Pyroptosis In Proliferation and Metastasismentioning
confidence: 99%
“…However, pyroptosis does not exert an absolutely positive therapeutic anticancer effect. A study revealed that elevated expression of GSDMC is also strongly associated with a worse prognosis for invasive breast carcinoma patients and exhibits a correlation with immune cell infiltration in the tumor [122]. Jianwei Gao and colleagues also found that increased GSDMD expression levels may increase the tumor size, promote more advanced tumornode-metastasis stages, and affect survival rates.…”
Section: Pyroptosis In Proliferation and Metastasismentioning
confidence: 99%
“…Recent studies have shown 28 that GSDMC and PD-L1 can cause BC tissue necrosis by transforming apoptosis into pyroptosis under hypoxic conditions. In addition, Sun et al 45 revealed that high expression of GSDMC leads to poor prognosis and tumour immune invasion in BC. CASP9 is an essential therapeutic target for various apoptosis-related diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sun et al. 45 revealed that high expression of GSDMC leads to poor prognosis and tumour immune invasion in BC. CASP9 is an essential therapeutic target for various apoptosis‐related diseases, including cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al ( 34 ) also found that GSDMC may be a risk factor for breast cancer prognosis. Sun et al ( 35 ) showed that the LINC00511/hsa-miR-573 axis could regulate the high expression level of GSDMC and that upregulated GSDMC was associated with a poor prognosis in patients with breast cancer. Zhang et al ( 36 ) showed that the oxidation of plasma membrane-localized death receptor 6 was induced by the enhancement of ROS and recruited both pro-caspase-8 and GSDMC to the cytosol, which activated GSDMC cleavage by caspase-8, thus inducing pyroptosis.…”
Section: Gsdmcmentioning
confidence: 99%